Phase separation and self-assembly of cyclic amphiphilic block copolymers with a main-chain liquid crystalline segment1. Issue 22 (14th June 2015) - Honda, Satoshi; Koga, Maito; Tokita, Masatoshi; Yamamoto, Takuya; Tezuka, Yasuyuki
<x xml:space="preserve">Abstract</x> The effects of the macrocyclization of amphiphiles with a liquid crystalline segment were investigated in the solid state, and electric field-responsive cylindrical micelles and vesicles were self-assembled.